If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -3b = 6c Solving 5a + -3b = 6c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3b' to each side of the equation. 5a + -3b + 3b = 3b + 6c Combine like terms: -3b + 3b = 0 5a + 0 = 3b + 6c 5a = 3b + 6c Divide each side by '5'. a = 0.6b + 1.2c Simplifying a = 0.6b + 1.2c
| 6x-7=2x+12 | | 5z+17z=176 | | Z=-24 | | 3x+4y-2+x+5y+3=0 | | 6x+6+x=3+2x-7 | | 3m+27=57 | | m/9+10=16 | | 5x*3f= | | 11k+6=39 | | 0.3x-2.8=4.9 | | w^2-7wf-18f^2= | | 12k+3=63 | | N=.05x-98.75 | | 6w-5=25 | | 8a-10=22 | | 2x+5=2(4+x) | | y=-10x | | -5x-18=7 | | 1.25x-3.34=7 | | 2x+4(x-8)=3(2x+12) | | (2m+9)(m-7)=0 | | =x^2+40x-100 | | -2x-6-3x=1 | | 0.67x-3.5=2.25 | | =2x^2+8x+8 | | x=2+0.5y | | =2x^2 | | 2k+4=10 | | =x^2-100x+2500 | | x=-4-9(-1) | | 3x+7-9x=2(8x-5) | | v^2+5v-9= |